The Effect of Financial Literacy, Risk Perceptions, and Social Media on Investment Decisions of The Millennials in Padang City - Yola Purnama Sari; M. Fany Alfarisi; Rida Rahim (Dinasti Research, 2024)
The purpose of this research is to analyze the factors that influence the investment decisions of the millennials in Padang City. Investment decisions are an important thing that an investor must consider when investing in the stock market. The population in this research is the entire millennial generation of Padang City, specifically people born in 1980-2000 who became investors in the stock market. The analysis method used is descriptive statistical analysis and factor description analysis using SmartPLS 4.0. The research results show that financial literacy, risk perception and social media have a positive and significant effect on investment decisions.